A P2P overlay system for network anomaly detection in ISP infrastructures - Silva, Miguel (2019)
This paper presents a P2P Overlay system for network anomaly detection, providing ISP network administrators with a versatile, easily configurable and useful tool to monitor the network infrastructures. In this context, this document describes the system general architecture and the main entities that integrate the proposed overlay system. Some technical details of the system will be provided, along with particular aspects of a real implementation of a system prototype, which was made using the JAVA language. The robustness and usefulness of the devised solution is proven resorting to the CORE network emulator platform. Such platform allows emulating a real ISP network infrastructure, over which a prototype of the proposed overlay system and integrating entities is tested and the corresponding results analysed. Some illustrative use cases of the system operation will be also presented and analysed.